Respostas

2013-09-22T19:36:20-03:00
A.(-3)+b=9        -3a+b=9    Multiplicando por -1  3a-b=-9 Resolvendo o sistema: 8a=-16     
a.(5) +b=-7        5a+b=-7                                  5a+b=-7                                   a=-16/8 
                                                                                                                       a=-2
                                                                                    
                        -3.(-2)+b=9      A função é -2x+3,substituindo:
                           6+b=9            f(1)= -2.1+3
                               b=9-6         f(1)= -2 + 3 = 1
                               b=3            f(1)=1